Protection versus flexibility: a critical analysis of the new labour brokering provisions introduced by the 2014 amendments to the Labour Relations Act, 66 of 1995 - Masimbe, Tawanda (Department of Commercial Law, 2016)
The paper will focus primarily on Labour Law with a particular emphasis being placed on the amendments to the LRA that deal with labour-broker employees. In order to fulfil this endeavour, the perceived purpose of labour law will be looked at to inform a discussion of what the amendments should be aiming to achieve. Further reference will also be made to fundamental International Labour conventions in order to enlighten the analysis.